Zwei neue Isoplia-Arten aus Westafrika (Coleoptera: Lamellicornia, Melolonthidae, Rutelinae). - Machatschke, Johann W. (Contributions to Entomology = Beiträge zur Entomologie, 1960)
There are described two new species of the genus Isoplia from West-Africa (Isoplia ganganicola and Isoplia freyi), and compared with the species hitherto known (Isoplia lasiosoma Burmeister). Nomenclatural Acts freyi Machatschke, 1960 (Isoplia), spec. n. ganganicola Machatschke, 1960 (Isoplia), spec. n.